Relaxation‐compensated APT and rNOE CEST‐MRI of human brain tumors at 3 T. Issue 2 (29th March 2019) - Goerke, Steffen; Soehngen, Yannick; Deshmane, Anagha; Zaiss, Moritz; Breitling, Johannes; Boyd, Philip S.; Herz, Kai; Zimmermann, Ferdinand; Klika, Karel D.; Schlemmer, Heinz‐Peter; Paech, Daniel; Ladd, Mark E.; et al.
Abstract : Purpose: Relaxation‐compensated CEST‐MRI (i.e., the inverse metrics magnetization transfer ratio and apparent exchange‐dependent relaxation) has already been shown to provide valuable information for brain tumor diagnosis at ultrahigh magnetic field strengths. This study aims at translating the established acquisition protocol at 7 T to a clinically relevant magnetic field strength of 3 T. Methods: Protein model solutions were analyzed at multiple magnetic field strengths to assess the spectral widths of the amide proton transfer and relayed nuclear Overhauser effect (rNOE) signals at 3 T. This prior knowledge of the spectral range of CEST signals enabled a reliable and stable Lorentzian‐fitting also at 3 T where distinct peaks are no longer resolved in the Z‐spectrum. In comparison to the established acquisition protocol at 7 T, also the image readout was extended to three dimensions. Results: The observed spectral range of CEST signals at 3 T was approximately ±15 ppm. Final relaxation‐compensated amide proton transfer and relayed nuclear Overhauser effect contrasts were in line with previous results at 7 T. Examination of a patient with glioblastoma demonstrated the applicability of this acquisition protocol in a clinical setting. Conclusion: The presented acquisition protocol allows relaxation‐compensated CEST‐MRI at 3 T with a 3D coverage of the human brain. Translation to a clinically relevant magnetic field strength of 3 T opens the door to trials with a large number of participants, thus enabling a comprehensive assessment of the clinical relevance of relaxation compensation in CEST‐MRI.